2017
DOI: 10.1111/pedi.12523
|View full text |Cite
|
Sign up to set email alerts
|

Associations between major life events and adherence, glycemic control, and psychosocial characteristics in teens with type 1 diabetes

Abstract: Aims: This cross-sectional study assessed the type of major life events occurring in a contemporary sample of teens with type 1 diabetes and the association between event frequency and demographic, diabetes management, and psychosocial characteristics.Methods: Parents of 178 teens completed the Life Events Checklist to report major events teens had experienced in the last year: 42% experienced 0 to 1 event (n = 75), 32% experienced 2 to 3 events (n = 57), and 26% experienced 4+ events (n = 46). Teens and paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
(27 reference statements)
0
17
0
Order By: Relevance
“…We found that HbA1c was significantly increased among children who experienced three or more adverse events (9.66% (12.8 mmol/mol) versus 8.19% (66.0 mmol/mol); β: 0.63 (4.5 mmol/mol); 95% CI: 0.11-1.15 (1.08-10.2 mmol/mol); p = 0.02). Similarly, Commissariat et al showed that among 178 teens with T1DM, glycated hemoglobin was higher in those who experienced more stressful life events [17]. We also found that the HbA1c was 0.62% (4.4 mmol/mol) higher in children who lived with a household member who had served time in jail, and 0.71% (5.4 mmol/mol) higher in those who had witnessed or had been a victim of violence in the neighborhood, when compared to those who did not have such exposure.…”
Section: Discussionmentioning
confidence: 93%
“…We found that HbA1c was significantly increased among children who experienced three or more adverse events (9.66% (12.8 mmol/mol) versus 8.19% (66.0 mmol/mol); β: 0.63 (4.5 mmol/mol); 95% CI: 0.11-1.15 (1.08-10.2 mmol/mol); p = 0.02). Similarly, Commissariat et al showed that among 178 teens with T1DM, glycated hemoglobin was higher in those who experienced more stressful life events [17]. We also found that the HbA1c was 0.62% (4.4 mmol/mol) higher in children who lived with a household member who had served time in jail, and 0.71% (5.4 mmol/mol) higher in those who had witnessed or had been a victim of violence in the neighborhood, when compared to those who did not have such exposure.…”
Section: Discussionmentioning
confidence: 93%
“…As a result, adolescents may avoid taking responsibilities of self-management of diabetes and lead to unsuccessful glycemic control. Commissariat et al’s [ 10 ] study confirmed that increased conflicts between parents and adolescents may lead to poorer adherence and lower self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Literature has shown that better self-management in adolescents increased the likelihood of achieving good glycemic control [ 7 , 8 , 9 ]. However, studies also revealed that many adolescents with T1D did not achieve good glycemic control [ 10 , 11 , 12 ]. It is critical for healthcare providers to gain an in-depth insight into the experience of adolescents with T1D self-management of blood glucose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other issues that might be important to screen for include stressful life events, as youth with more stressors have poorer quality of life, treatment adherence, and glycemic outcomes. 43 After deciding on the constructs to measure in a screening protocol, an important consideration is the selection of instruments to use. Sequential screening is one option to integrate both features: individuals who screen high on a highly sensitive measure then complete a second screener with high specificity, and those who score high on both receive further evaluation by a clinician.…”
Section: Selecting Measuresmentioning
confidence: 99%